AGE AND GROWTH, LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION FACTOR OF PENAEUS SEMISULCATUS DE HAAN - Thomas, M M (Indian Journal of Fisheries, 2011)
Determination of age and growth of Penaeus semisulcatus de Haan wasmade by Peterson's method. Since the spawning in this species is prolonged,the modes tend to overlap as the growth ^ows with age. So, a size group couldbe traced only as far as possible after its entry into the coounercial fishery. Theave^e moodily growth rate in different stages, and from this, the approximatevalues at various ages were computed.